Buscando respuestas al reto de la diversidad desde la pedagogía crítica - Paulette Barberousse-Alfonso (Universidad Nacional, Costa Rica, 2003)
Rethinking diversity from the point of view of critical pedagogy constitutes one of the main challenges of contemporary education, given that we all must assume the topic of altering in times of globalization and post-modernism. The same diversity which is present in society, is also a specific factor at school. The problem is that diversity in society is considered as inequality and at school it means diversity, which can mask "pedagogical" inequalities. We must rebuild and rethink school from the diversity for equality under the mandate of compensating inequalities.